Are All Foreign Policy Innovators Created Equal? The New Generation of Congressional Foreign Policy Entrepreneurship. Issue 2 (1st June 2016) - Marsh, Kevin; Lantis, Jeffrey S
Abstract: This study revisits Carter and Scott's model of congressional foreign policy entrepreneurship (2004, 2009, 2010) to evaluate how a new generation of legislative innovators, including Senators Rand Paul and Ted Cruz, may influence US foreign policy. Specifically, this study proposes two new types of foreign policy entrepreneurs in Congress—"revolutionaries" and "mercenaries"—and examines their different motivations, policy objectives, and strategies to attempt to influence or change state behavior. Case evidence suggests that in a new era of partisanship and polarization, more complex models of players, strategies, and measures of success are needed.